Women’s empowerment and child nutrition in the Asia – Pacific region: Evidence from Papua New Guinea, Sri Lanka, and Timor-Leste - Leight, Jessica; Mukerjee, Rishabh; Kala, Peggy (International Food Policy Research Institute, 2025)
Adverse nutritional outcomes for children under five remain a significant challenge around the world, and there is growing evidence that women’s empowerment is associated with better children’s nutritional outcomes. In this paper, we analyze the association between women’s empowerment and the probability of stunting, wasting, underweight status, and achieving dietary diversity for children under five using a cross-country sample of Demographic and Health Survey data from three countries in the Asia – Pacific region: Papua New Guinea, Sri Lanka, and Timor-Leste. We construct the Survey-based Women’s Empowerment (SWPER) index as well as a slightly modified SWPER index using women’s reported experience of intimate partner violence (IPV) rather than attitudes toward domestic violence (employed in the original index). Our findings suggest that women’s empowerment as captured by the SWPER index is associated with a reduced incidence of stunting, wasting and underweight status and a higher probability that children achieve MDD, though this relationship is only weakly observed in Timor-Leste. In general, the index estimated using experience of IPV shows a clearer association with nutritional outcomes, vis-a-vis the index estimated using attitudes toward IPV.